Illegal fishing and maritime security: towards a land- and sea-based response to threats in West Africa - Lewerenz, Catharina (SWP Comments, 2015)
West African coastal states lose up to $1.5 billion a year as a result of illegal fishing. The effects of overfishing also hit these countries hard. In its Strategy on the Gulf of Guinea, the European Union highlights the threats and risks posed to these coastal states, as well as the connections to Europe as an export market for fishery products and home region of many fishing vessels. Until now, maritime security strategies for West Africa have prioritized the issues of human trafficking, smuggling of migrants, and piracy. In future, however, there should be a stronger focus on the threats posed by illegal fishing, especially when providing advice, training and equipment assistance to improve surveillance and monitoring of West African waters. An integrated approach is required, which should also address the onshore problems associated with the fisheries sector. (Autorenreferat)